A Study on the Impact of Mobile Devices on First Year University Students - Balfagih, Hasan (Auckland University of Technology, 2017)
The hand held mobile devices (e.g. mobile phones, Ipads and tablets) are becoming popular resources to enhance student learning in tertiary education settings. However, these smart devices have become more of an accessory and toys rather than being communication devices. Tertiary teachers and educators would like to know the impact of use of mobile devices in the classrooms on academic performance of tertiary students. Although there are few research studies investigating the impact of mobile devices on student learning and comprehension, but an in-depth study on the negative aspect of use of these mobile devices is still an unexplored area. In fact, we do not have enough evidence to make comments on whether students are using or misusing mobile devices in the classrooms. The proposed research aims to study the effectiveness of the use of mobiles devices on academic performance of tertiary students. The results of the study will help in recommending practices to balance the negative impact of mobile devices on academic performance of students. The effectiveness of the use of mobile devices will be evaluated through student survey data (using questionnaire) as well as staff and student interview. A cross comparison with survey data collected from Saudi Arabia and the US will also be presented. A set of recommendations will be made that help teachers to manage the class more effectively for enhanced student learning.
Keywords: Mobile phones; Ipads and tablets; The effectiveness of the use of mobile devices; Smart devices; Help teachers to manage the class more effectively for enhanced student learning.